IDENTITY AS AN OBJECT OF STUDY SOCIAL SCIENCES: A PHENOMENOLOGICAL APPROACH - Коriakovtseva, Olga; Bugachuk, Tatyana; Dosse, Tatyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The transformation of Russian society provoked a new round of interest in the social sciences, including the growth of defined research on the formation of social identity, an important place in the structure which occupies a civic identity. The scientific article is devoted to research of problems of identity in terms of "existential crisis". The authors define the specifics of social and civic identity based on a phenomenological approach.